Switzerland : Detailed Assessment of Compliance-Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This Detailed Assessment of Compliance on the Basel Core Principles for Effective Banking Supervision on Switzerland discusses that significant portions of guidance and legislation related to qualitative risk management and control standards are not as detailed or comprehensive as in many other major countries and need to be updated and selectively strengthened. Supervisory risk assessments and guidance to auditors, as the extended supervisory arm of the Swiss Financial Market Supervisory Authority (FINMA), need to be further materially improved, beyond what is now envisioned. Additional skilled resources within FINMA are necessary to meet these goals and to conduct more on-site supervisory work. The responsibilities and objectives of FINMA that emphasize protecting creditors, investors and insured persons, as well as ensuring proper functioning of the financial market, should be clearly stated in legislation as pre-eminent. It is recommended to increase FINMA resources, especially for on-site inspection and risk expertise. Clarify and limit the cases in which the Board can become involved in supervisory decisions and improve conflict code.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet